Mapping quantitative trait loci related to nodule number in soybean (Glycine max (L.) Merr.) in response to the Sinorhizobium (Ensifer) fredii HH103 NopT type III effector. Issue 1 (1st January 2021) - Liu, Yanru; Sun, Mingzhe; Chen, Qingshan; Xin, Dawei; Sun, Xiaoli
ABSTRACT: Type III effectors play a vital role in the establishment of symbiosis. In this study, positive and negative effects of NopT on nodulation were detected in 30 soybean germplasms. The quantitative trait loci (QTL) related to nodule number were identified and their responses to NopT in recombinant inbred lines and chromosome segment substitution lines were evaluated. Ten QTL were identified on chromosomes 02, 05, 06, 10, and 13. One overlapping region on chromosome 02 was responsive to the wild-type rhizobium and the NopT mutant. The expression patterns of the genes in this overlapping region were determined and single nucleotide polymorphisms and haplotypes were analyzed to identify the candidate genes. Four candidate genes were identified as significantly responsive to NopT. Glyma.02G135100 and Glyma.02G100800 expression levels were directly affected by NopT. These results form the basis of future efforts to identify the plant host genes affected by type III effectors.